Factors affecting the intention to donate money for waqf among civil servants in the Ministry of Religious Affairs - Widodo, Jennifer Selviana; Darma, Emile Satia (Journal of Accounting and Investment, 2025)
Research aims: This study examines the factors that influence the intention of cash waqf for the state civil apparatus of the Ministry of the Religion of the Banjarnegara district by examining the influence of accountability, transparency, crowdfunding platform security, and reputation of the Indonesian waqf agency.Design/Methodology/Approach: This study involved the state civil apparatus of the Ministry of Religion in the Banjarnegara district. Hypotheses were tested using SEM-PLS techniques.Research findings: The results showed that transparency and accountability did not significantly affect state civil servants' intention to endow money. At the same time, the security of the crowdfunding platform and the reputation of the Indonesian waqf agency have a significant positive effect on the intention to endow money.Theoretical contribution/Originality: The novelty of this research is to exploreand comprehensively analyze how the influence of accountability, transparency, and crowdfunding platform security reputation of the Indonesian waqf agency builds cash waqf intentions for state civil apparatus at the Ministry of Religion.Practitioner/Policy implication: Based on this insight, it is hoped that building cash waqf intentions for the state civil apparatus is not only in the Ministry of Religion but is comprehensive for all ministries and city/district governments Indonesian waqf agencies as managers of cash waqf funds can carry out all tasks by considering accountability, transparency, crowdfunding platform security a reputation on.Research limitation/Implication: The implementation of transparency, accountability, and crowdfunding platform security and reputation, the primary purpose of which is to build intention to donate money, is still insufficiently implemented. In addition, the underlying process of how Badan Wakaf Indonesia collects and presents cash waqf information is crucial.